2014
DOI: 10.1212/wnl.0000000000001029
|View full text |Cite
|
Sign up to set email alerts
|

Explanatory factors for the increased mortality of stroke patients with depression

Abstract: Objective: To identify explanatory factors for the association between depression and increased mortality up to 5 years after stroke. Methods:In this cohort study, data from the South London Stroke Register (1998)(1999)(2000)(2001)(2002)(2003)(2004)(2005)(2006)(2007)(2008)(2009)(2010)(2011)(2012)(2013) were used. Patients (n 5 3,722) were assessed at stroke onset. Baseline data included sociodemographics and stroke severity. Follow-up at 3 months included assessment for depression with the Hospital Anxiety and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
60
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(66 citation statements)
references
References 30 publications
1
60
1
1
Order By: Relevance
“…However, findings tended to contradict studies which have shown anxiety to be more prevalent among younger stroke survivors (Ayerbe et al, 2014;Castillo et al, 1993;Schultz, Castillo, Kosier & Robinson, 1997). One explanation may be that, since stroke is infrequent in younger cohorts, such an event may cause greater emotional distress in such cohorts (Petrea et al, 2009); however, it is recognised that the mixed sample included in the current study (i.e.…”
Section: Discussioncontrasting
confidence: 71%
See 1 more Smart Citation
“…However, findings tended to contradict studies which have shown anxiety to be more prevalent among younger stroke survivors (Ayerbe et al, 2014;Castillo et al, 1993;Schultz, Castillo, Kosier & Robinson, 1997). One explanation may be that, since stroke is infrequent in younger cohorts, such an event may cause greater emotional distress in such cohorts (Petrea et al, 2009); however, it is recognised that the mixed sample included in the current study (i.e.…”
Section: Discussioncontrasting
confidence: 71%
“…In preference to psychiatric diagnoses, these studies have increasingly explored anxiety via the use of self-report tools such as the Hospital Anxiety and Depression Scale (HADS; Zigmond & Snaith, 1983). In one such study -which involved a synthesis of predictors and associated outcomes of anxiety (up to 10 years after stroke) - Ayerbe et al (2014) reported prevalence rates ranging from 32-38%. Notably, in this study, 58% of patients were assessed as suffering from clinically significant levels of anxiety at 3 months post-stroke.…”
Section: Anxiety In the Aftermath Of Abimentioning
confidence: 99%
“…34-2.20). 57 This study should be interpreted with caution because numerous models were used to describe the association between depression and mortality, and the only common factors between these models were age, sex, ethnicity, and stroke severity. The relationship between SSRIs and mortality requires a rigorous analysis of the interactions with other key variables such as depression, disability, and comorbid medical conditions.…”
Section: Association Between Psd and Mortalitymentioning
confidence: 93%
“…The most common neuropsychiatric complication after stroke, post-stroke depression (PSD), has been linked with increased mortality and morbidity whereas involuntary emotional expression disorder, including pathological crying (PC), another relatively common complication seen in many neurological disorders, is often socially disabling [1][2][3] . Treatment with antidepressants, in particular treatment with selective serotonin reuptake inhibitors (SSRIs), is often used in the treatment of both depression and PC after stroke [4][5][6][7] and has been linked with increased mortality in some, but not in all studies [8][9][10][11] . However, SSRIs have also been associated with a reduced risk of recurrent ischemic events and better functional outcome after stroke [12][13][14] .…”
Section: Introductionmentioning
confidence: 99%
“…However, SSRIs have also been associated with a reduced risk of recurrent ischemic events and better functional outcome after stroke [12][13][14] . Other previous studies have focused on long-term mortality associated with SSRI treatment initiated up to 1 year after stroke [11,15] . To our knowledge, there are no large-scale populationbased studies on the effect of early antidepressant treatment after ischemic stroke.…”
Section: Introductionmentioning
confidence: 99%